Entrepreneurship education : insights into students’ learning experience / Kaarthiyainy Supramaniam and Nalini Arumugam - Supramaniam, Kaarthiyainy; Arumugam, Nalini (ACRULeT, Faculty of Education & UiTM Press, 2012)
Entrepreneurship education is emerging as an important field that it is timely to closely examine the learning experiences of individuals who are immersed in a formal curriculum to inculcate entrepreneurship. There is a lack of insights into how the teaching methods adopted in the top-down approach affect students’ learning experiences. This paper adopts a case study approach in investigating an event organised by undergraduates at a Malaysian public university as universities in the local context heed the call to produce more entrepreneurs to spur socio-economic activities. Observations and interviews with the student leader and two other students, and their lecturers revealed that while the top-down approach preferred by the university in engaging students to spur them to become entrepreneurs has its merits, the response at the ground level revealed challenges that they faced in participating in the entrepreneurial event. Findings of the study underscore the importance of narrowing the gap between pedagogical prescriptivism and learner readiness to become entrepreneurs.